Prevention and Management of Venous Thromboembolism - Jesslyn, Jesslyn; Putri Amalia, Putri Amalia (The Indonesian Journal of General Medicine, 2024)
Background: The literature on the prevention and management of venous thromboembolism (VTE) reveals significant advancements and ongoing challenges in clinical practice. A foundational article emphasizes the necessity for early recognition of VTE symptoms and timely intervention to prevent severe complications such as pulmonary embolism and post-thrombotic syndrome. Literature Review: The need for multifaceted strategies to improve compliance with VTE prevention protocols is underscored, particularly as many at-risk patients do not receive adequate prophylaxis. Specific at-risk populations, such as pregnant women, the elderly, and obese patients, face unique challenges in VTE prevention and management. The critique of suboptimal prophylactic measures in these groups emphasizes the urgent need for tailored risk assessment tools and adherence to clinical guidelines. Innovative approaches, such as the integration of clinical decision support systems, are explored as potential solutions to improve adherence to VTE prevention protocols. The complexities of managing VTE risk in clinical settings necessitate evidence-based strategies to enhance patient outcomes, particularly in light of declining hospital lengths of stay. Conclusion: In conclusion, the literature underscores the evolving understanding of VTE prevention and management, emphasizing the critical need for comprehensive strategies that address both clinical and systemic barriers to effective prophylaxis and treatment. Enhanced education, tailored risk assessments, and the integration of decision support systems are vital to improving adherence to established protocols and ultimately reducing VTE-related complications.